2020
DOI: 10.1002/andp.202000028
|View full text |Cite
|
Sign up to set email alerts
|

Magnon Blockade in a PT‐Symmetric‐Like Cavity Magnomechanical System

Abstract: We investigate the magnon blockade effect in a paritytime (P T) symmetric-like three-mode cavity magnomechanical system involving the magnon-photon and magnon-phonon interactions. In the broken and unbroken P T-symmetric regions, we respectively calculate the second-order correlation function analytically and numerically and further determine the optimal value of detuning. By adjusting different system parameters, we study the different blockade mechanisms and find that the perfect magnon blockade effect can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Moreover, such magnetomechanical systems support mode hybridization not only between magnons and phonons but also between magnons and microwave photons, which further enriches the system dynamics. Since then, various novel physi-cal phenomena or applications based on magnetomechanical interactions have been proposed or experimentally studied, including magnon blockade, 49 phononmediated magnon entanglement, 50 magnetomechanical squeezing, 51 magnon-assisted ground state cooling of phonon state, 52 etc.…”
Section: B Magnetomechanics and Magnon-phonon Coupled Devicesmentioning
confidence: 99%
“…Moreover, such magnetomechanical systems support mode hybridization not only between magnons and phonons but also between magnons and microwave photons, which further enriches the system dynamics. Since then, various novel physi-cal phenomena or applications based on magnetomechanical interactions have been proposed or experimentally studied, including magnon blockade, 49 phononmediated magnon entanglement, 50 magnetomechanical squeezing, 51 magnon-assisted ground state cooling of phonon state, 52 etc.…”
Section: B Magnetomechanics and Magnon-phonon Coupled Devicesmentioning
confidence: 99%
“…Furthermore, an important triple-resonance condition is possible, where the phonon frequency matches the difference in frequencies between the hybrid cavity-magnon modes [22], allowing selective cavity enhancement of scattering processes. This triple-resonance system has sparked significant interest, resulting in theoretical proposals for the generation of non-classical entangled states [23][24][25][26][27][28], squeezed states [29][30][31], classical and quantum information processing [32][33][34][35][36], quantum correlation thermometry [37], and exploring PT -symmetry [38][39][40][41]. Many of these proposals rely on the ability of the external drive to act on the mechanical motion, so called dynamical backaction.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the method to generate magnon blockade by modifying their energies, Wang et al reported unconventional blockade in the absence of nonlinearities, by playing with the magnon-photon coupling strength, the gain of the cavity and loss of the magnet to generate a  symmetric system [189]. In such a case, different channels interfere which leads to a significant occupation of the single magnon energy level.…”
Section: Single Magnon Statementioning
confidence: 99%